#BlackLivesMatter and Feminist Pedagogy: Teaching a Movement Unfolding - Goldthree, Reena N.; Bahng, Aimee (Radical Teacher, 2016)
What are the stakes of teaching #BlackLivesMatter simultaneously in New Hampshire and in the national media? We draw upon our experiences leading two iterations of a #BlackLivesMatter course at Dartmouth College to consider the feminist pedagogical origins of “experiential learning,” the intersectional dynamics of enacting a teaching collective, and working in dialogue with the movement itself.